The Influence of Competence, Time Budget Pressure, Professionalism, and Work Experience on Audit Quality: An Empirical Study at Public Accounting Firms in South Jakarta - Pramudyaning Sari, Sophie; Hendrawan, Agus (Dinasti Publisher, 2025)
The purpose of this study is to examine the influence of competence, time budget pressure, professionalism, and work experience on the audit quality produced by auditors. The research was conducted at Public Accounting Firms (KAP) located in South Jakarta. Using a quantitative approach, data were collected through questionnaires distributed to auditors working at Public Accounting Firms listed in the IAPI public accounting firm directory for the year 2025, using a purposive sampling technique. The data were analyzed using multiple linear regression with the assistance of SPSS version 30. The results indicate that competence, professionalism, and work experience have a positive and significant effect on audit quality, while time budget pressure has a negative effect. These findings suggest that improving auditors’ competence, professionalism, and experience can enhance audit quality, whereas excessive time pressure may reduce it.